2009
DOI: 10.1080/14789940802638341
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence recidivism in high-risk Taiwanese offenders after the completion of violence treatment programs

Abstract: A case-control trial enrolled 70 high-risk domestic violence (DV) offenders under protective orders and court-ordered batterer treatment (study group) and 231 low-medium risk DV offenders under protective orders only. Recidivism was defined as any recurrence of violence by the offenders. These acts of violence included both physical and verbal violence, which were measured by interviewing the victims by telephone at three, six, and nine months after mandatory treatment for the study group or after adjudication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
5
15
0
1
Order By: Relevance
“…For instance, in a recent study based on a population with 336 male and female victims of IPV, Rahman (2018) reported that 43% were victimized repeatedly within 12 months. Similar numbers were presented in Lin et al (2009); 48% of the offenders relapsed into overall violence within 3 months. Petersson and Strand (2017) compared rates of IPV recidivism among antisocial and family-only offenders.…”
Section: Introductionsupporting
confidence: 77%
“…For instance, in a recent study based on a population with 336 male and female victims of IPV, Rahman (2018) reported that 43% were victimized repeatedly within 12 months. Similar numbers were presented in Lin et al (2009); 48% of the offenders relapsed into overall violence within 3 months. Petersson and Strand (2017) compared rates of IPV recidivism among antisocial and family-only offenders.…”
Section: Introductionsupporting
confidence: 77%
“…Twelve of the 13 patients showed significant improvement, which was maintained on 2-year follow-up. The abnormal representation of learning disabilities, ADHD, head injuries, childhood abuse, alcoholism, and substance abuse in an incarcerated offender population (Wekerle & Wall, 2002;Wilson & Cumming, 2009) and of alcoholism and drug abuse in domestic violence (Lin et al, 2009) would suggest considerable potential for the use of neurofeedback, particularly given the high recidivism rates that attest to the limited effectiveness of traditional psychotherapies and pharmacology treatment. This will be another fruitful area for further research.…”
Section: Alcoholism and Substance Abusementioning
confidence: 99%
“…El porcentaje de reincidentes en este estudio es similar al obtenido en trabajos previos en los que se analiza la reincidencia durante el año posterior a la finalización de la intervención (Eckhardt, Holtzworth-Munroe, Norlander, Sibley, & Cahill, 2008;Kingsnorth, 2006;Lin et al, 2009;Loinaz, 2014), aunque no se encontraron diferencias significativas entre los participantes con PCA y los que no tienen PCA.…”
Section: Discussionunclassified